Direct‐Ink‐Write 3D Printing of Programmable Micro‐Supercapacitors from MXene‐Regulating Conducting Polymer Inks. Issue 9 (12th January 2023) - Li, Le; Meng, Jian; Bao, Xuran; Huang, Yunpeng; Yan, Xiu‐Ping; Qian, Hai‐Long; Zhang, Chao; Liu, Tianxi
Abstract: 3D printing is gaining prospects thanks to the ease of manufacturing energy storage devices with programmable geometry at the macro‐ and microscales. Herein, a direct ink writing 3D printing approach for preparing all‐printed flexible micro‐supercapacitors is demonstrated using rationally designed poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS)/MXene composite gels as inks without the tedious processes and toxic organic additives. Among the printable inks, the homogeneously distributed MXene nanosheets can boost the printability of PEDOT:PSS solution and also regulate the interconnected electronic structures of the PEDOT:PSS undergoing a micellar to linear structure transition. The resulting 3D printed micro‐supercapacitors and integrated devices can deliver exceptionally large areal capacitances, remarkable rate performance, and high cycling stability with thickness‐independent capacitances even under exceptional deformations and low temperatures. This study thus provides a simple yet environmental‐friendly approach for preparing the conducting‐polymer‐based inks for 3D printing of customized, multiscale, and integrated energy devices. Abstract : A direct‐ink‐write 3D printing approach for preparing all‐printed flexible micro‐supercapacitors is presented by using rationally designed poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate/MXene composite gels as the printing ink. The 3D printed micro‐supercapacitors and their integrated devices can deliver exceptionally large areal capacitances, remarkable rate performance, and high cycling stability with thickness‐independent capacitances even under exceptional deformations and low temperatures.